Evaporative drying pattern of graphite nanoparticles in binary base fluids - Chua, Gabriel Wee Kiat (2014)
Nanofluids can be simply expressed as fluids that contain nanoparticle suspensions. The addition of these nanoparticles helps to improve the fluid properties significantly, causing nanofluids to gain popularity and be adopted for a wide variety of industrial applications such as cooling devices in electronics when used in conjuncture with thin film evaporation. As the field of nanofluids is still relatively unexplored, this study aims to elucidate the evaporation characteristics of graphite nanofluids in particular by varying several parameters that are thought to affect these characteristics. The primary nanofluids used in this study comprises of graphite nanoparticles suspended in a binary mixture of ethanol (25 wt%) and distilled water. Results were recorded by varying several factors such as the nanoparticle and surfactant concentrations. Coffee ring thickness was found to share a directly proportional relationship with both the droplet diameter and the nanoparticle concentration, regardless if surfactants were added or not. An interesting development in the duration of this study would be the appearance of a donut pattern upon complete nanofluid evaporation. While the exact reasoning behind is phenomenon is still uncertain, initial experiments show a close relationship between the formation and elapsed time after nanofluid preparation. Finally, nanoparticle velocity during the evaporation process was also found to increase with respect to time and reach a maximum near the end of the process.